Surveillance Protocol for the Detection of Intracranial Abnormalities by Cranial Ultrasonography in Premature Neonates - Ahmed Mahmoud Mohamed Elsayed; Walaa Mohamed Elnaggar (2022)
(3jJYQV GdCWaGd MOjKj GdhdGOI dNWQ GdEUGHI HEUGHGJ GdOeGZ , Ydi GdQZe ef GdJbOe GdedMhX aj QYGjI GdCWaGd MOjKj GdhdGOI bO COi Edi JMSf cHjQ aj HbGA hfJGFL gDdGA GdeQVi GdeYQVjf ddNWQ , EdG Cf EUGHGJ GdOeGZ dG JRGd eUOQ bdb cHjQ(B. (3GdJUhjQ HGdehLGJ ahb GdUhJjI ddeN gh Jbjje ege dJbOjQ GdMGdI GdYUHjI ddGWaGd MOjKj GdhdGOI , ShGA cGfJ aj hLhO CYQGV Ch HOhf hLhO CYQGV(B. (3CLQjJ gPg GdOQGSI Ydi (B100 (3Wad ef GdGWaGd MOjKj GdhdGOI GdPjf Je LeYge ef QYGjGJ MOjKj GdhdGOI HeSJTai GdCWaGd HLGeYI GdbGgQI daMU GdGWaGd MOjKj GdhdGOI GdehdhOjf bHd GdGSHhY GdQGHY h GdKdGKjf ef GdYeQGdQMej Phj GdNWhQI GdYGdjI HGSJNOGe GdehLGJ ahb GdUhJjI Ydj GdLeLeI aj GdCSHhY GdChd ef GdYeQ(B. (3hLOJ fJGFLfG Cf (B36 (3% dOjge JNWjW ZjQ WHjYj HGdehLGJ ahb GdUhJjI aj GdLeLeI Ydi Tcd fRja OGNd GdLeLeI (B(28 (3%(B) (3, hGYJdGd OeGZj fJjLI fbU GdGcSLjf (B(4 (3%(B) (3, hGJSGY GdHWjf (B(2 (3%(B) (3, hJThg OeGZj (B(1 (3%(B) (3hVYa GdeGOI GdHjVGA Mhd GdHWjf (B(1 (3%(B). (3GdeXGgQ GdYUHjI HeG aj Pdc fbU JhJQ GdYVdGJ , fbU QOhO GdYVdGJ GdYUHj , GdQVGYI GdVYjaI , GdjGahN GdCeGej GdhGSY hGdJTfLGJ cGfJ ehLhOI CcKQ HTcd edMhX Hjf MOjKj GdhdGOI GdPjf jYGfhf ef GdJUhjQ HGdehLGJ ahb GdUhJjI ZjQ GdWHjYj(B. (3CXgQJ fJGFL eJGHYI GdJUhjQ HGdehLGJ ahb GdUhJjI Cf GdfSHI GdeFhjI dfRja GdeN RGOJ ef (B26(3% Edi (B35(3% HjfeG Hbj fbU GhcSLjf GdeN HfaS GdfSHI hCf cdG ef aTd ai Jchf aUjf GdeN hGNJdGd GdbTQI GdHjVGA ddeN cGf dgeG faS GdfJGFL aj GdeJGHYI ajeG jJYdb HfSHge , HjfeG (B1 (3abW ef Hjf MOjKj GdhdGOI dG jRGd dOjge HWjfGJ LGfHjI eJhSYI (B(1(3%(B).s
Thesis (M.Sc.)-Cairo University,2022.
Bibliography: p. 100-73.
Keywords: Pediatrics; preterm neonates